The Impact of Ease of Digital Access on the Increase in Online Gambling Cases Among Students - Saefullah, Rifki; Vaidyanatahan, Sundarapandian (International Journal of Ethno-Sciences and Education Research, 2025)
This study investigates the relationship between ease of digital access and increasing online gambling participation among Indonesian university students. Through a quantitative descriptive approach involving 420 respondents from various universities, the research examines how technological advancement has influenced gambling behavior among students and its multidimensional consequences. The findings reveal a significant correlation between digital accessibility and gambling participation, with 43.3% of respondents having engaged in online gambling and 25.9% remaining active gamblers. Students with easy digital access were nearly three times more likely to gamble online compared to those with limited access. Demographic analysis showed higher participation rates among male students and those residing in urban areas with superior digital infrastructure. The research identified substantial negative impacts on participants, including psychological effects (76.4% experiencing stress and anxiety) and academic consequences (56.6% reporting decreased concentration). Despite 62% of students claiming moderate digital literacy, only 28% demonstrated true understanding of digital risks, revealing a critical gap between technical proficiency and risk awareness. The majority of gambling-involved students (67.2%) reported first encountering gambling through social media platforms, highlighting the influential role of digital marketing in normalizing gambling behavior. This study underscores the need for comprehensive interventions including enhanced digital literacy education, campus-based support services, strengthened regulatory frameworks, and innovative prevention campaigns targeting digital-native students. The research contributes to understanding how rapidly evolving digital ecosystems create unprecedented challenges in academic environments and offers strategic recommendations for institutional and governmental responses to protect student welfare and academic success.